2013
DOI: 10.1021/jp407397y
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Blue Organic Light-Emitting Diodes Based on Intermolecular Triplet–Singlet Energy Transfer

Abstract: Diphenilamino-substituted carbazoles were used as guest compounds for the preparation of highly efficient blue organic light-emitting diodes based on the phenomenon of delayed fluorescence. It was shown that the spectra of the delayed fluorescence of host−guest systems are identical to those of the prompt fluorescence and in general coincide with the photoluminescence spectra of the guest films. The congruence of the prompt and delayed fluorescence spectra is explained by the effective intermolecular triplet−s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 25 publications
0
48
0
Order By: Relevance
“…Because of the covalent linkage between the chromophores there is no need to use the acceptor dye at high concentrations that is needed for efficient energy transfer in case of double-doped OLEDs. [32,33] Usually heavy atoms are required to get significant emission from the triplet state. Here we have shown that by using the described tandem luminophore strategy heavier atoms than sulfur were not required for construction of bright orange or red organic emitters possessing PL decay time in microsecond or millisecond range.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the covalent linkage between the chromophores there is no need to use the acceptor dye at high concentrations that is needed for efficient energy transfer in case of double-doped OLEDs. [32,33] Usually heavy atoms are required to get significant emission from the triplet state. Here we have shown that by using the described tandem luminophore strategy heavier atoms than sulfur were not required for construction of bright orange or red organic emitters possessing PL decay time in microsecond or millisecond range.…”
Section: Discussionmentioning
confidence: 99%
“…[31,32] Phosphor-sensitized fluorescence in devices comprising of two purely organic compounds was demonstrated in 2013. [33] In these double-doped OLEDs intermolecular, long-range, non-radiative energy transfer from the phosphorescent sensitizer to the fluorescent dye was used to increase efficiency of the device. However, to date there is no general strategy for the application of interfluorophore TSET for construction of efficient organic triplet emitters.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the efficiency of OLED based on tetraoxa [8]circulenes is insufficiently high compared to other analogues based on carbazole derivatives, the brightness of which is 15 times higher (reaches 12 500 cd m 72 ). 132 The efficiency of OLED doped with Ir III complexes 133 ± 138 is even higher (the brightness can be as high as 56 900 cd m 72 based on the [Ir(ppy) 3 ] complex, where Hppy is 2-phenylpyridine) 139,140 than that of OLED based on tetraoxa [8]circulenes. 32 This is associated primarily with the insufficiently efficient energy transfer from the (4,4 H -N,N H -dicarbozolyl)biphenyl matrix to tetraoxa [8]circulene molecules.…”
Section: New Materials Based On Hetero[8]circulenesmentioning
confidence: 99%
“…31 The consequence for such LUMO level, lying clearly below --2 eV, should be an easier electron injection from the cathode during the device operation. 32 Photoelectrical Properties. The ionization potential (I p ) of the solid film of 3 was estimated from the photoelectron emission spectra (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%